2018
DOI: 10.1111/ejn.14281
|View full text |Cite
|
Sign up to set email alerts
|

Repeated blast model of mild traumatic brain injury alters oxycodone self‐administration and drug seeking

Abstract: Each year, traumatic brain injuries (TBI) affect millions worldwide. Mild TBIs (mTBI) are the most prevalent and can lead to a range of neurobehavioral problems, including substance abuse. A single blast exposure, inducing mTBI alters the medial prefrontal cortex, an area implicated in addiction, for at least 30 days post injury in rats. Repeated blast exposures result in greater physiological and behavioral dysfunction than single exposure; however, the impact of repeated mTBI on addiction is unknown. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 74 publications
10
28
0
Order By: Relevance
“…The acquisition in the males was consistent with that observed using similar procedures in a group of experimentally naïve adult males (Nguyen et al, 2019). Unfortunately the majority of rat oxycodone IVSA studies published so far have been in male rats (Austin Zamarripa et al, 2018;Blackwood et al, 2019;Bossert et al, 2018;Jordan et al, 2019;Leri and Burns, 2005;Mavrikaki et al, 2019;Nawarawong et al, 2018;Neelakantan et al, 2017;Nguyen et al, 2019;Nguyen, J. D. et al, 2018b;Pravetoni et al, 2014;Townsend et al, 2017;Wade et al, 2015;You et al, 2018;You et al, 2017); one exception was a study in pregnant rats (Vassoler et al, 2018). Interestingly, when female animals were evaluated on a fentanyl dose substitution under an FR procedure, the THC exposed rats self-administered more drug at the lowest dose (Figure 9).…”
Section: Discussionsupporting
confidence: 84%
“…The acquisition in the males was consistent with that observed using similar procedures in a group of experimentally naïve adult males (Nguyen et al, 2019). Unfortunately the majority of rat oxycodone IVSA studies published so far have been in male rats (Austin Zamarripa et al, 2018;Blackwood et al, 2019;Bossert et al, 2018;Jordan et al, 2019;Leri and Burns, 2005;Mavrikaki et al, 2019;Nawarawong et al, 2018;Neelakantan et al, 2017;Nguyen et al, 2019;Nguyen, J. D. et al, 2018b;Pravetoni et al, 2014;Townsend et al, 2017;Wade et al, 2015;You et al, 2018;You et al, 2017); one exception was a study in pregnant rats (Vassoler et al, 2018). Interestingly, when female animals were evaluated on a fentanyl dose substitution under an FR procedure, the THC exposed rats self-administered more drug at the lowest dose (Figure 9).…”
Section: Discussionsupporting
confidence: 84%
“…We have previously demonstrated that our blast model of mild TBI leads to enduring microstructural changes in the medial prefrontal cortex 13 , a brain region critically involved in drug seeking in humans and rodent models (reviewed in [14][15][16] ). We have also found that repeated blast mild TBI (rbTBI) persistently elevated levels of oxycodone seeking, despite similar levels of prior drug self-administration 17 . In the current study, we hypothesized that rbTBI and oxycodone self-administration would lead to persistent changes in structure and/or function of the medial prefrontal cortex which may also extend to other aspects of mesocorticolimbic circuitry that would be associated with elevated drug seeking.…”
Section: Introductionmentioning
confidence: 80%
“…Rats were exposed to repeated blast overpressure or repeated sham conditions as described in 13,[17][18][19] . During blast or sham treatment, rats were maintained under anesthesia with a continuous delivery of 1.5% isoflurane and administered Rimadyl (carprofen, 5 mg/kg, s.c., Zoetis Inc, Kalamazoo, MI, USA).…”
Section: Repeated Blast Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Another promising translational approach targets issues relevant to predisposition and comorbidity. For example, compared with sham‐exposed rats, repeated blast traumatic brain injury (TBI)‐exposed rats were more sensitive to oxycodone‐associated cues during reinstatement, suggesting that repeated blast TBI may disrupt the relationship between oxycodone intake and seeking (Nawarawong et al ., ). Inflammation in the frontal cortex may be one underlying mechanism, as suggested by a study using TBI to expose to cocaine self‐administration (Vonder Haar et al ., ).…”
Section: Preclinical Modelsmentioning
confidence: 97%